Women in the International Film Industry: Policy, Practice and Power - Liddy, Susan (Springer International Publishing, 2020)
Keywords: Irina

The Women of Publishing Say #MeToo - Deahl, Rachel; Maher, John; Milliot |, Jim (PublishersWeekly.com)
Despite its image as a bastion of liberal thinking and its unusually high percentage of female workers, the publishing industry still has a significant sexual harassment problem.
Keywords: Irina

Title IX, Esports, and #EToo - Stoever, Jane K (The George Washington Law Review, 2021)
As colleges and universities increasingly award video gaming scholarships, field competitive esports teams, construct esports arenas in the centers of campuses, and promote student interaction through gaming, schools should anticipate the sexual cyberviolence, harassment, and technology-enabled abuse that commonly occur through gaming.
Keywords: Bibliographie; Irina; Nettoyer

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

A More Pixelated Union: A Look at the Path to Unionization in the Video Game Industry under Trump's National Labor Relations Board - Selfridge, William C. (2021)
Keywords: Irina

The #E-Too Movement: Fighting Back Against Sexual Harassment in Electronic Sports - Holden, John T; Iii, Thomas A Baker; Edelman, Marc (ARIZONA STATE LAW JOURNAL)
Competitive video gaming or esports has captured the attention of hundredsof millions ofpeople acrossthe globe. With that attentionhas come billions of dollars' worth of investment and promotion. But, it has also exposed an underlying toxic environment that features widespreadsexual andgender harassment. This pervasive culture of harassment threatens to derailthe esports industry and mars the promise of gender equity in one of the few competitive "sports"where physical strength, agility and body size do not dictate success. In this Article, we examine the rise of competitive gaming, and provide an in-depth analysis of the pervasive issue of harassment that permeates esports. We then propose a series of tangible reforms that would hold harassers and their corporate accomplices accountablefor their harassingbehavior.
Keywords: Irina

Speaking in Public: What Women Say about Working in the Video Game Industry - De Castell, Suzanne; Skardzius, Karen (Television & New Media, 2019)
Since the 1990s, conversations about the dearth of women working in the video game industry have centered on three topics: (1) ways to draw more women into the field, (2) the experiences of women working in the industry, and (3) the experiences of those who once worked in the industry but left. Although there has been considerable research on the conditions and occupational identities of video game developers, less scholarly attention has been devoted to women in gameswork, the barriers/obstacles and challenges/opportunities they face, and how they talk about their experiences. This article offers a feminist approach that demonstrates how discourse focused on affect can be reread as intimately related to silences about power and how the rhetorical constraints that public speech imposes upon what can be said about “women in games” aid us in understanding what might remain unspoken, and why.
Keywords: Bibliographie; Irina; Nettoyer

Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Hanussek, Benjamin (Press Start, 2022)
Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion, by Alayna Cole and Jessica Zammit. 2020. CRC Press. xv + 95 pp.
Number: 2
Keywords: Irina; diversity; game industry; game studies; inclusion

Exploring Vicarious Liability to Remedy the #E-Too Movement - Hewson, Eloise (York Law Review, 2022)
The esports, or competitive video gaming, industry is an exciting area of economic and cultural growth. Gaming can facilitate interpersonal connection, shared problem-solving, and creativity. Players may purchase a game, watch a streamer play it online, join an online gaming community, attend a tournament, compete professionally, or find employment in game development or a related field. The gaming industry generates enormous economic value and employs tens of thousands of people in the UK alone. However, the esports sector does not extend its benefits equally. Women are regularly verbally harassed in video games, countless women have been groped at esports events, women have been raped by professional players, underage fans have been groomed. Abuse is endemic to online gaming communities.
Keywords: Bibliographie; Irina; Nettoyer

Narrating women workers’ perceptions of sexism and change in the Australian screen postproduction sector before and after #MeToo - Dooley, Kath; Erhart, Julia (Feminist Media Studies, 2021)
This article interrogates the localized experiences of present-day workers who identify as women in Australian postproduction sectors, including editing, visual effects (VFX), and animation, exploring sex ism and perceptions of change in the age of #MeToo. Considering the significant numbers of women working in these sectors, and the scant research into their experiences undertaken in an Australian context, the authors conducted semi-structured interviews with ten women in various roles and in various geographical locations in Australia. This qualitative approach to data collection aims to explore inequalities that may not be captured in industry surveys, providing fine-grain details of the ways that individuals in postproduction experience sexism. The resulting data suggests that while there is continuity between the gendered experiences of these workers and that of women in industry sectors that have already been documen ted, there are, however, new observations about changes in work place behavior in the sector, brought about by growing public awareness of industry discrimination and harassment and of shifts in Australian industry policy. The authors isolated recurring themes within women’s gendered experiences in relation to how they per ceived the impact of the gender-equity initiatives on the attitudes of their co-workers, their workplace opportunities, and their experi ences as workers.
Keywords: Irina

The Routledge Companion to Romantic Love - Brooks, Ann (Routledge, 2021)
Keywords: Irina

Working with “monstrous men”: ambivalent sexism in the Bombay film industry - Sanchez Lozoya, Zeltzyn Rubi (Feminist Media Studies, 2022)
In India, the 2012 Delhi gang rape case catalyzed protests for women’s rights, particularly in regard to their safety. These demands were rekindled with vigor anew with the eruption of the #MeToo movement. In the Indian film industry, the most visible change appeared in the gradual increase of films with womenleads. But behind the scenes, there has been comparatively less change in female representation. Currently, approximately less than 10% of film directors in India are women. Considering the impor tance of having stories about women being made by women, in this article I examine the factors that hinder women’s entrance and tenure in the Mumbai film industry. I argue that a composite of concerns, including but not limited to reputability and personal security, thwarts women’s progress in the industry. I base my con clusions on interviews with women and men working in the film industry, conducted in Mumbai in 2017. I use the framework of the Ambivalent Sexism Index developed by psychologists Glick and Fiske in 1996, and revised in 2013, (1996, 2001, 2013) to examine my interviewees’ encounters with hostile and benevolent sexism. This article complicates our understanding of the reasons that limit the work of women beyond explanations of overt discrimination.
Keywords: Irina

Critical Analysis of Sexual Harassment at Work Place (Prevention, Prohibition and Redressal) Act, 2013 with Special Emphasis to Film Industry - S', Anjana; George, Meera Elsa
Gone are the days where only men were the breadwinners of a family. With opportunities expanding and people moving forward into a contemporary world, gender disparity regardingemployment has become a thin line. We are in an era where both men and women workfor a living and contribute to theirfamily. Women are now coming forward and stepping into powerful positions and leaving their marks in various industries. However, there are many issues that demotivate women from coming forward. One such major issue is the absence of a healthy and safe working environment. Sexual Harassmentat Workplace is a violation of a woman's fundamental rights under Article 15, 19 and 21. It makes a woman insecure and causes severe mental trauma which in turn makes her quit the job or affects her self-confidence. Women are not sex toys for pleasure or the weak vulnerable section of humankind, but years of the patriarchalsystem that silenced women have resultedin women being subject to such exploitation.
Keywords: Irina

#metoo: The Good, the Bad, and the Backlash - Tranchese, Alessia (From Fritzl to #metoo: Twelve Years of Rape Coverage in the British Press, 2023)
I start this discussion in this chapter with an outline of the key points within the #metoo debate, looking at what, according to various scholars, has and has not been achieved since the hashtag went viral in 2017. This overview constitutes the context for the subsequent analysis and critical evaluation, which will look at how the press conceptualised #metoo, and how it shaped some of the wider discussions about the hashtag. In Chapter 11, it will focus on whether (and how) the widespread use of #metoo after 2017 affected the representation of violence against women in the British press compared to the previous years.
Keywords: Irina

Designing Women: Learning from Feminist Legacies and the Women-In-Games Movement - Schoemann, Sarah (Georgia Institute of Technology, 2021)
In 2019 the video games industry was rocked by a slew of high-profile sexual harassment and assault allegations that some called the #MeToo movement of the games world, but to many these revelations came as no surprise. From the 2004 EA Spouse controversy to the 2014 #Gamergate harassment campaign the games industry has long been known for harboring an at times toxic atmosphere of exploitation and discrimination. This project looks at a handful of Women-In-Games organizations that set out to change the experience of women in the industry by helping newcomers to gain high tech skills and to supporting early career professionals through mentorship and community building. Along the way, it combines the study of these Women-In-Games organizations with a years-long collaboration bringing video games to the US' oldest feminist bookstore, Charis Books & More in Atlanta, GA. Through examining the work and values of two types of organizations devoted to women's equality, one a historic feminist movement-building space and the others, contemporary interventions into the professional games and tech industry, this study asks the questions "What can the Women-In-Games movement learn from the rich history of feminist organizing at spaces like Charis?" "Can games play a part in feminist movement building?" and "What does the future of feminist organizing look like in the games industry?”
Accepted: 2021-09-15T15:43:41Z Publisher: Georgia Institute of Technology
Keywords: Bibliographie; Irina; Nettoyer

Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Cole, Alayna; Zammit, Jessica (CRC Press, 2020)
Description Cooperative Gaming provides context and practical advice regarding diversity in the games industry. The book begins with a deep dive into research literature and the history of diversity in the games industry to provide context around what diversity is and why it is a topic worth considering. The book looks at the different facets of diversity and games, exploring the issues and solutions within game development, studio management, event planning, and more. It provides people with practical advice about being a marginalized person in the games industry and how to be heard, how studios can support inclusive practices, and events can actively become more accessible to a diverse audience. Key Features • Explores the history of diversity in games • Provides important information around what it is like to be a marginalized person in the industry • Gives practical steps to improve the inclusivity of the industry that are designed to aid in contextualizing and upskilling new developers Author Bios Alayna Cole is the managing director of Queerly Represent Me, a not-for-profit championing queer representation in games. Alayna is also a producer at Sledgehammer Games, co-chair of the IGDA LGBTQ+ special interest group, and an award-winning games journalist and game developer. She was featured on the 2016 and 2017 Develop Pacific 30 Under 30 lists and the 2017 and 2019 Develop Pacific Women in Games lists, and she has received several other accolades in the industry. Jessica Zammit started writing in 2013 for Start Select Media, and for the next five years she followed her interest in writing about representations of mental health, diversity, and particularly, sexuality in video games. Jessica has been speaking about diversity in games at conventions such as PAX Australia since 2016 and has been featured on several other discussions in and around the topic of representation in games and games criticism. Along with her co-author, she is co-chair of the IGDA LGBTQ+ special interest group, and she was featured on the 2018 Develop Pacific 30 Under 30 and Women in Games lists.
Google-Books-ID: 0XjtDwAAQBAJ
Keywords: Computers / Programming / Games; Irina

Let Her Play: A report on gender-based violence in video games - Mettler, Kirsten (Embodied: The Stanford Undergraduate Journal of Feminist, Gender, and Sexuality Studies, 2022)
Globally, video games are a $152 billion industry, and approximately 3.1 billion people, or 40% of the population, are players (Ingersoll & Anti-Defamation League, 2019, Price, 2020). Gaming is a huge industry, and it’s only getting bigger. Unfortunately, women and other historically marginalized groups often face staggering levels of harassment and violence in these communities. This report aims to explore the issue of gender-based violence in video games by analyzing contributing factors and proposing gaming company interventions.
Number: 1
Keywords: Bibliographie; Irina; Nettoyer; esports

#MeToo, Time's up, and Theories of Justice - Wexler, Lesley; Robbennolt, Jennifer K.; Murphy, Colleen (I) (University of Illinois Law Review, 2019)
Keywords: Irina

The impact of intervention measures on sexual harassment in the film and television industry - Eng, Ben; McKinney, Ralph; Shao, Lawrence (Journal of International Management Studies, 2019)
Since 2017, increased sexual harassment incidents have been reported in Hollywood; yet, little guidance has been offered on how organizations, which are informally governed by their network members, can effectively reduce sexual harassment. Building upon the theory of network governance, this paper suggests social mechanisms, which are used to coordinate and safeguard exchanges between Hollywood organizations, are more effective at reducing incidents of workplace sexual harassment than traditional strategies. These social mechanisms direct change to the macroculture through collective sanctions that damage the perpetrators reputation and restrict access to network opportunities. In essence, perpetrators become toxic assets that Hollywood avoids and this avoidance is similar to economic sanctions that can deter sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

Understanding Sexual Harassment in the #MeToo Era - Julios, Christina (Sexual Harassment in the UK Parliament: Lessons from the #MeToo Era, 2022)
This chapter provides a contextual account of the rise of #MeToo as an global gender-equality campaign supporting those affected by sexual transgressions. Originally articulated by African-American civil rights activist Tarana Burke in 2006, the slogan ‘me too’ was meant as a rallying cry to support young minority ethic survivors of sexual abuse. Years later, social media would turn Burke’s motto into a byword for the global #MeToo movement. The chapter chronicles the events surrounding #MeToo’s inception, including Hollywood producer Harvey Weinstein’s sexual exploitation scandal in 2017, and The New York Times and The New Yorker exposés of his serial offending within the film industry. It also examines the narratives of countless survivors and #MeToo campaigners, including high-profile cases such as those of Rose McGowan, Alyssa Milano, Mimi Haleyi, Jessica Mann and Zelda Perkins. The chapter then critically considers the growth and international significance of #MeToo as well as its inherent shortcomings.
Keywords: #MeToo; Farrow; Harvey Weinstein; Irina; Kantor and Twohey; Rose McGowan

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - Gürkan, Hasan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Keywords: Irina

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Reconceptualizing Sexual Harassment, Again Collection: #MeToo and the Future of Sexual Harassment Law - Shultz, Vicki (Yale Law Journal Forum, 2018)
Keywords: Irina

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change: Sexual harassment in the creative industries - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments’ policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands’ creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors inﬂuenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-speciﬁc research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.
Keywords: Bibliographie; Irina; Nettoyer

Hard facts, soft measures: Gender, quality and inequality debates in Danish film and television in the 2010s - Redvall, Eva Novrup; Sørensen, Inge Ejbye (Journal of Scandinavian Cinema, 2018)
Abstract This article investigates discussions about gender, quality and equality in Danish film and television in the 2010s. Contrary to Sweden, where gender diversity has been part of public debate and formal screen policy since the 2000s, there was little discussion of gender in the Danish screen industry until the Danish Film Institute (DFI) began focusing on diversity as a priority area before the Film Strategy for 2015–18. The article analyses how both DFI and industry players have continuously argued against gender quotas, instead opting for soft measures such as ‘gender declarations’ and initiatives to raise awareness. One of these initiatives was a manifesto, ManusFestet, that used humour to raise questions about gender representation on-screen. The article discusses how a balance between hard facts and soft measures seems to be experienced as a constructive way forward, as long as this combination does in fact facilitate the intended change.
Publisher: Intellect
Keywords: Irina

Now About All These Women in the Swedish Film Industry - Wallenberg, Louise; Papadopoulou, Frantzeska; Koskinen, Maaret; Soila, Tytti (Bloomsbury Academic, 2023)
In the aftermath of the MeToo movement, during an ongoing pandemic, and in the midst of repeated demands for a 50/50 split between men and women in above-the-line positions, this book analyzes and interrogates the politics of gender focusing on the Swedish film industry, often considered to be the most "gender equal" film industry worldwide. While this gender equality (with a considerable proportion of women behind the camera) is much due to policies carried out of the state funded Swedish Film Institute, women filmmakers in Sweden still struggle with the same problems as do women in other national film industries. These problems entail having smaller production and distribution budgets than men and working in an environment involving recurring scandals of gender discrimination and sexual harassment. This open access book looks behind the statistics and explores the often complex cultural, legal, and political conditions under which women have entered a male-dominated industry and discusses women’s strategies and efforts to promote change while providing evidence on how women’s presence has challenged the industry by provoking critical reactions and introducing new ways to portray women on screen. Using a wide range of different sources (e.g. archival material, laws, contracts, films, biographical materials, and interviews), the book tells the history of the rise of gender equality efforts undertaken by the Swedish Film Institute and investigates women’s possibilities to manage the rights to their work. It offers compelling portraits of pioneering women who have worked in or in relation to the industry and looks at the experiences of women currently working in the film industry. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Örebro universitet.
Accepted: 2023-02-09T13:06:14Z
Keywords: Irina; Metoo; Sweden; Swedish Film Institute; TV & radio::APF Films; change; cinema::APFA Film theory & criticism; cinema::APFN Film: styles & genres; conditions; discrimination; equality; film industry; filmmakers; male-dominated; pioneering; politics of gender; rights; scandal; sexual harassment

Gendered Precarity and Labor Organizing in the South Indian Film Industries - Mini, Darshana Sreedhar
Keywords: Irina

The impact of #MeToo in the South African film and television industry, within a historical framework - Majiba, Ntsika (Université de l'Afrique du Sud, 2022)
The study is a history project and is concerned with tracking the impact of #MeToo in the South African Film and Television industry in South Africa. Its main premise were the findings made public by a South African organization, Sisters Working in Film and Television (SWIFT) in 2017, that found that sexual harassment in the television and film industry was not just a norm but a crisis. The core focus of the study was on the development and impact of the #MeToo movement, which entailed investigating the manner in which women reacted to the hashtag (#MeToo), the reaction of their male counterparts, as well as the reaction and actions taken by the various bodies, institutions and organisations in the Film and Television industry, which included; broadcasters and production houses alike. This study begins by giving a concise background of the movement by firstly, historicising various female-led movements and comparing and contrasting them with the rise of digital movements or digital activism. The historicisation involves a brief comparison of past and present women-led activism, as well as a brief review of other hashtags like #AmINext and #Enough, on which #MeToo has had an influence. It goes on to investigate the development of #MeToo movement and to discuss the responses of the industry and individuals to the movement. The study embarked on a data collection quest by interviewing eleven female television and film practitioners in South Africa. Their ages ranged from 20 to 55. The findings of the research revealed that female practitioners were still being harassed post #MeToo, although subtly. The lack of unity amongst women in the sector was cited as one of the reasons behind the ongoing harassment. Gender parity and equity was also still lacking in the South African television and film industry. This study emerged in the midst of activism and scholarship seeking to unravel the norms of South African sexual harassment and rape culture against women. Thus, the study focused on the changes and transformations brought about by the hashtag within the industry. With South Africa’s historical background and the current circumstances around Gender Based Violence (GBV), this study was concerned with tracking whether or not digital activism had in some way been able to aid change and transformation. In particular, this study looked at the impact of the MeToo phenomenon on the women in the industry, the extent to which it empowered them, what they began to say and how they began to act. The study also explored South Africa’s ‘rape culture’ as South Africa has been proclaimed the ‘worlds rape capital’. It reflected on the colonial rule as the perpetuation of patriarchy and male entitlement over female bodies. Patriarchy in the industry was also confirmed by the findings and through data analysis, as one of the key factors in the emergence of #MeToo in South Africa, and in the utilisation of the hashtag by women in the sector to speak up against sexual harassment.
Accepted: 2023-02-20T11:59:11Z
Keywords: Bibliographie; Irina; Nettoyer

Experiencing Male Dominance in Swedish Film Production - Jansson, Maria; Wallenberg, Louise (Women in the International Film Industry: Policy, Practice and Power, 2020)
Sweden has been hailed for its recent success in increasing the number of female directors, scriptwriters and producers. Published reports, panel discussions and a vast number of press conferences on the pressing matter of gender equality within the industry together with a 5050 quota have all put the Swedish film industry—and its CEO Anna Serner—on the map. However, the last couple of years has disclosed several scandals regarding sexism and discrimination in the Swedish film industry—just as in other national film industries. This paper sets out to discuss how female film workers (e.g., directors, actors and producers) understand and negotiate their experiences of male dominance within their work context. Based on a series of interviews with women working in Swedish film from the early 1960s until today, we analyze similarities and differences in experiences as well as how these experiences are explained by the interviewees. Their stories are analyzed by using feminist institutional theory to understand how policy, funding schemes and other institutional aspects are intertwined with their experiences. The paper sets out to analyze three themes: (1) comments and suggestions during production and post-production regarding female protagonists; (2) experience of gender trouble in the process of fundraising; and (3) strategies used by the interviewed filmmakers to produce a more women-friendly environment during productions.
Keywords: Irina

Gender Equality in British Film-making: Research, Targets, Change - Cobb, Shelley; Williams, Linda Ruth (Women in the International Film Industry: Policy, Practice and Power, 2020)
In October 2017, the British Film Institute declared that it would commit to specific targets for gender equality and diversity in key production roles on films with support from the Film Fund. This decision by the BFI to set targets, arguably, did not come just from their own diversity and inclusion goals. Activist film-makers had previously called for targets for the Film Fund, especially for women directors. This chapter will give an accounting of the current state of gender (in)equality in the UK industry by: outlining new research that has clarified the stagnant inequality in the UK film industry; articulating the key role of a network of activist groups (that include researchers, professional and campaigning bodies, exhibitors and film-makers) to bring attention to the problem; putting pressure on the film industry and public bodies; and summarising institutional responses to that pressure since 2016, with a critical analysis of the potential and limits of the BFI’s relatively recently implemented diversity and equality targets.
Keywords: Bibliographie; Irina; Nettoyer